Liegnitzer, Hundsfeld or Lew? The question of authorship of popular Medieval fighting teachings - Jaquet Daniel; Walczak Bartłomiej (Acta Periodica Duellatorum)
In numerous 15th and 16th century Fightbooks several sets of teachings appear alongside the glosses of Liechtenauer’s Epitome on armoured fighting and fighting on horseback (Harnischfechten and Rossfechten) often enough to be considered auctoritas on these subjects. However, their authorship from various witnesses are attributed to different authorial figures - Andreas Liegnitzer, Martin Hundsfeld, Jud Lew.